GENETIC DIVERSITY ANALYSIS IN RELATION TO SEED YIELD AND ITS COMPONENT TRAITS IN INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS) - Cluster analysis; G. C. JADEJA; JOGENDRA SINGH; RAMESH (The Bioscan, 2014)
In any crop imrovement programme, the choice of genetically divergent parents for hybridization is dependent upon categorization of breeding materials on the basis of appropriate criteria. A total of 60 genotypes of Indian mustard (Brassica juncea L. Czern and Coss) were evaluated in Randomized Block Design with two replications during 2011-2012 rabi season to study genetic diversity using Mahalanobis D² statistics for seed yield and its components. The 60 genotypes were grouped into 13 clusters based on D² analysis. The maximum inter-cluster distance (D) was found between cluster VI and VII (824.53), followed by that between VI and XI (798.76). The minimum inter-cluster distance was observed between cluster II and XII (99.24). The intra-cluster distance (D) ranged from 75.43 (cluster-III) to 113.18 (cluster-VI). The attributes, viz., seed yield per plant (27.33%), number of siliqua per plant (24.13%) and length of main branch (21.17%) contributed much to the total genetic divergence. On the basis of cluster means, cluster XII (34.84) was superior for seed yield per plant, whereas cluster XI was good for number of secondary branches per plant (27.67), number of seeds per siliqua (16.45) and protein content (32.22). The cluster VIII had desirable rating in respect of days to 50% flowering (48.00), days to maturity (111.00) and length of main branch (127.20), while the maxima for number of primary branches per plant (8.67) and number of siliqua per plant (564.00) were observed in cluster VII. Cluster IX was the best for test weight (5.07 g) and plant height (189.00 cm). Therefore, intercrossing of such genotypes involved in these clusters would be useful for generating variability for the respective characters, and their rational improvement for increasing the seed yield per plant.